Primary Adrenal Leiomyosarcoma: Case Report and Review of Literature - Azzouni, MD, Faris; Azabdaftari, MD, Gissou; Safwat, MD, Mohab; Schwaab, MD, PhD, Thomas (North American Journal of Medicine and Science, 2012)
Primary adrenal leiomyosarcomas are rare and usually symptomatic at presentation. The presentation of a large adrenal mass should raise suspicion of adrenal leiomyosarcoma as a differential diagnosis. To our knowledge, primary adrenal leiomyosarcoma has been reported in 20 cases in the English literature. Here we describe a case of primary adrenal leiomyosarcoma in a 76-year-old Caucasian female. The patient complained of right upper quadrant abdominal pain for 2 months. Contrast-enhanced magnetic resonance imaging showed a heterogeneous 10.5 cm adrenal mass with a suspected inferior vena cava tumor thrombus without lymph node enlargement or distant metastasis. The patient underwent a right adrenalectomy, partial resection of the inferior vena cava and reconstruction of the inferior vena cava with a pericardial patch. Histopathologic examination was consistent with leiomyosarcoma. At 3 months postoperatively, a follow-up computed tomography scan of the chest, abdomen and pelvis without intravenous contrast was done that showed multiple bilateral pulmonary metastatic lesions, bilateral hilar and mediastinal lymphadenopathy, liver metastasis, a new mass at the head of the pancreas, and a new mass at the lower pole of the right kidney. The patient was deemed to be unfit for systemic chemotherapy, and was referred to the hospice service for palliative care. The patient died 4 months after surgery.